AUDIT MUTU HUKUM PENGATURAN DAN PENERAPAN PERATURAN DAERAH PROVINSI JAWA BARAT TENTANG PERTANGGUNGJAWABAN SOSIAL - Novrizha Dinda Larasati; Tarsisius Murwadji; Deden Suryo Rahardjo (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
Corporate Social Responsibility (CSR) is a commitment from a company to contribute to the community around the company's operational area. The Local Government of West Java Province established a Regulation which regulates the implementation of CSR programs in West Java. This research aims to determine the regulation and application the CSR Program in West Java by using the audit of legal quality theory. This research is based on documents and activities such as the Regional Medium Term Development Plan document (RPJMD), and research in Nagrog Village. Based on the results of the research, the implementation of CSR has been carried out well and in accordance with the Regulations of West Java Province, although there are some deficiencies that can be corrected and developed. Keywords: Audit of Legal Quality, Corporate Social Responsibility, Local Government Regulation